Proxy Server dan Management Bandwidth Jaringan Komputer Menggunakan Mikrotik RB952Ui5ac2nD (Studi Kasus MA Ishlahul Ikhwan Nahdlatul Wathan Mispalah Praya) - Wira Bakti; Khairul Imtihan; Ahmad Susan Pardiansyah (LPPM STMIK Lombok, 2018)
The condition of existing networks in Madrasah Aliyah Ishlahul Ikhwan Nahdlatul Wathan Mispalah Praya network managers currently facing several challenges related to the existing internet connection point is a limited bandwidth connection and not proportional to the number of existing users. Internet connection utilization through Local Area Network at study hours, ie from morning to night. This policy has an impact on their complaints from teachers, students and not optimal internet connection services available. In addition to the lack of LAN network security used. With such a solution it is necessary to reduce the impact of internet connection instability on the Madrasah Aliyah Ishlahul Ikhwan Nahdlatul Wathan Mispalah Praya network by adding Mikrotik RB952Ui5ac2nd that serves as a proxy server, and bandwidth management. The purpose of this research is to improve LAN network security in Madrasah Aliyah Ishlahul Ikhwan Nahdlatul Wathan Mispalah Praya by adding mikrotik RB952Ui-5ac2nD, facilitate access to Internet by adding proxy server, and doing bandwidth distribution. Data collection method used is observation method, interview and literature study. From some of these methods will be analyzed network problems and create the required design, then test the new design results. The required equipment is Mikrotik RB952U-5ac2nD for proxy server and bandwidth management to generate blocking system design, increase internet access speed, and optimize bandwidth usage.